Usefulness of environmental information to bank officers in Malaysia - Mohd Said, Ridzwana; Sulaiman, Maliah; Nik Ahmad, Nik Nazli (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
Corporate social and environmental disclosure practices reflect corporate transparency and accountability towards wider stakeholders. Since information disclosure imposes huge costs upon companies, the usefulness of information to stakeholders is worth examining. Drawing from the notion of normative pressure of institutional theory, this study examined the usefulness of environmental information to bank officers in Malaysia. Several aspects of environmental information disclosure were examined, namely, companies’ environmental attributes, types of environmental information disclosed and forms of disclosure. The results revealed that bank officers perceived environmental information to be important in their lending decisions. We also tested the actual use of environmental information in the lending decisions of bank officers for which it was found that bank officers do not incorporate environmental information in their lending decisions. Accordingly, the notion of normative pressure of institutional theory is partly supported. The present study has important implications for corporate environmental reporting practices in Malaysia.